Quality of life and associated factors among patients with breast cancer under chemotherapy at Tikur Anbessa specialized hospital, Addis Ababa, Ethiopia - Hassen, Anissa Mohammed (PLoS One, 2019)
BACKGROUND: Breast cancer is the most common cancer affecting women in Ethiopia with increasing burden, and chemotherapy treatment produces a detrimental effect on individual wellbeing. Since last few years quality of life has been the primary goal of cancer treatment, yet little research has been conducted on quality of life of breast cancer patients under chemotherapy. OBJECTIVE: To determine the quality of life and associated factors among patients with breast cancer under chemotherapy at Tikur Anbessa specialized hospital, Addis Ababa, Ethiopia. METHODS: Institution based cross-sectional study was conducted on 404 patients with breast cancer, who took at least one cycle of chemotherapy treatment using face to face interview at oncology unit of Tikur Anbessa specialized hospital day care center from February to April 2018. The validated Amharic version of European organization for research and treatment of cancer core 30 (EORTC QLQ-C30) and quality of life questionnaire specific to breast (QLQ-BR23) was used to measure health related quality of life. Both descriptive and inferential statistics were used. For the purpose of interpretation quality of life score was dichotomized in to two using the calculated mean score, which is 53 as a cutoff point, then, bi-variable and multivariable logistic regression was used to describe association between dependent and independent variables. Hence, patients who score above 53 for quality of life were considered to have good quality of life. RESULT: Of the total sample, overall response rate was 99.77%. The average quality of life score of patients with breast cancer under chemotherapy treatment was 52.98 (SD = 25.61). Majority of patients had scored poor in emotional functioning, sexual functioning, and financial difficulties. Educational status of college and above, being divorced, higher household income, higher scores of physical and social functioning were associated with significantly improved (better) quality of life. Lower scores of fatigue, insomnia, financial difficulties and systemic therapy side effects all were associated with better scores of quality of life of breast cancer patients. Whereas, patients receiving < = 2 cycles of chemotherapy had significantly lower scores of quality of life. CONCLUSION AND RECOMMENDATION: Quality of life of breast cancer patients under chemotherapy treatment is poor in comparison with the reference data and international findings. Therefore, quality of life assessment should be incorporated in patient’s treatment protocol. And financial aids may significantly improve the quality of life of breast cancer patients under chemotherapy treatment.